Faktor-Faktor yang Mempengaruhi Tingkat Adopsi Teknologi Tanam Jajar Legowo Tanaman Padi di Kecamatan Kalianda Lampung Selatan - Evi Yulianti; Dame Trully Gultom; Helvi Yanfika (Jurnal Multidisiplin Indonesia, 2026)
The adoption of agricultural technology is an important strategy to increase rice productivity amid the decreasing availability of agricultural land. One innovation promoted by the government is the Jajar Legowo planting system, which has proven potential to improve rice yields. However, the level of adoption among farmers remains varied. This study aimed to analyze the level of adoption of the Jajar Legowo rice planting technology and identify the factors influencing its adoption among rice farmers in Kalianda District, South Lampung Regency. The research employed a quantitative approach with descriptive and inferential analyses. A total of 140 respondents were selected using proportional stratified random sampling. Data were collected through structured questionnaires and analyzed using descriptive statistics and multiple linear regression. The results showed that the adoption level of Jajar Legowo technology was categorized as high. Simultaneously, farmer characteristics, social factors, institutional factors, information sources, communication channels, and extension worker quality significantly influenced technology adoption. Partially, land size, social networks, farmer institution functions, and agricultural extension worker quality had a significant positive effect on adoption levels, while other variables were not significant. Social networks emerged as the most dominant factor influencing adoption. These findings imply that strengthening farmer institutions, expanding social networks, and improving extension service quality are essential to enhance the adoption of agricultural innovations and support sustainable rice productivity improvement.